PENGARUH PEMBERIAN TABLET TAMBAH DARAH (TTD) DAN JUS JAMBU BIJI MERAH TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI - Oktarina Listiani; Susi Tursilowati; Ria Ambarwati (JURNAL RISET GIZI, 2018)
Background  : Anemia experienced  by most young women in Indonesia. Supplementation of Fe tablet is given to young women in junior high and high school. The absorption of Fe tablet will be maximal if consumed along with vitain C. Guava juice is one of the fruit that contains vitamin C and become an alternative in increasing hemoglobin levels.Objective  : To know the effect of supplementation of Fe tablet and red guava juice to increase hemoglobin level in female adolescent at SMP PGRI 01 Semarang. Method  : This study uses Experimental Quasy with pre and post test design group control design. The number of research samples are 28 people consist of 14 treatment samples and 14 control samples. Data collected were general characteristics data of sample, anthropometric data, nutrient intake data (energy, protein, iron and vitamin C) and measurement data of Hb level. Statistical Analysis using Anova Repeated Measur with 95% confidence degree.Results  : The mean hemoglobin level in the treatment group was 10.7 g / dL, in the control group of 10.2 g / dL. While the mean hemoglobin level after giving intervention in the form of supplementation of Fe tablet and guava juice in the treatment group had 11,4 gr / dL average, in control group 10,6 gr / dL which was only given Fe tablet supplementation.Conclusion  : There were no significant differences but there was an increase between hemoglobin levels before and after supplementation of Fe tablets and guava juice in the treatment group and control group p = 0.728 (p 0.005), although it was controlled with adequate intake of energy, protein, vitamin C, iron and long menstruation.